2004
DOI: 10.1001/archsurg.139.5.552
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Comparative Safety of Colloids

Abstract: Hypothesis: Safety differences exist among colloids widely used for fluid management in acutely ill patients, as judged according to the comparative incidence of adverse events.Data Sources: Colloid safety data for human subjects were sought, without language or time period restrictions, by means of computer searches of bibliographic and clinical trial databases, hand searches of medical journals and Index Medicus, inquiries with investigators and colloid suppliers, and examination of reference lists. Search t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
101
1
11

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(113 citation statements)
references
References 109 publications
(147 reference statements)
0
101
1
11
Order By: Relevance
“…Many studies have reported about the anaphylactic reactions after polygeline infusion. 10,11 Other safety concerns reported with regard to polygeline use are coagulopathy and circulatory disturbances. [9][10][11]16 In one such study reported in Sweden between 1971 and 1977, 9 cases of anaphylactic reactions were observed.…”
Section: Shah S Et Al Int Surg J 2018 Apr;5(4):1432-1437mentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have reported about the anaphylactic reactions after polygeline infusion. 10,11 Other safety concerns reported with regard to polygeline use are coagulopathy and circulatory disturbances. [9][10][11]16 In one such study reported in Sweden between 1971 and 1977, 9 cases of anaphylactic reactions were observed.…”
Section: Shah S Et Al Int Surg J 2018 Apr;5(4):1432-1437mentioning
confidence: 99%
“…In contrast to the concerns reported by reviews and meta-analyses regarding the safety of polygeline, no ADRs or any unusual clinically significant changes were reported within 6 hours of polygeline administration in this study. [9][10][11]16 Worsening of symptoms due to any underlying medical history was not reported for any patient.…”
Section: Shah S Et Al Int Surg J 2018 Apr;5(4):1432-1437mentioning
confidence: 99%
“…24 The incidence of allergic reactions is greatest with gelatins and dextran, followed by HES, and least with albumin. 25 While the optimal fluid therapy for septic patients is undecided, crystalloid overload is known to be harmful. 26,27 Albumin is a scarce resource, very expensive, has the potential to transmit viral disease and may not be as physiologically beneficial as low molecular weight starch.…”
Section: Fluid Therapymentioning
confidence: 99%
“…Nustatyta, jog visi koloidai, išskyrus želatinos tirpalus, gali sukelti hiperonkotinį ūminį inkstų funkcijos nepakankamumą dėl tirpale esančių makromolekulių, kurios negali prasiskverbti per inkstų kanalėlius, todėl prasideda inkstų kanalėlių stazė ir obstrukcija, o sergantiesiems sepsiu hidroksietilkrakmolo dariniai yra ūminio inkstų funkcijos nepakankamumo rizikos veiksnys (3,5,9). Sergančiuosius inkstų funkcijos nepakankamumu gydant krakmolo tirpalais, gali pasireikšti portinė hipertenzija ir ascitas (10,12).…”
Section: Nepageidaujami Reiškiniaiunclassified